DEFINING SHARĪʿAH-COMPLIANT TOURISM - Abdul Qadir, Abu Hassan Makmun; Yusnaidi, Yusnaidi; Devilishanti, Tio; Yuliana, Desi; Hasni, Jusnaini (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
The increasingly lucrative Muslim market has caught much attention from Muslim and non-Muslim tourism service providers. They have begun offering services and products that suit the demands and needs of Muslims, while still maintaining their non-Muslim clienteles. Different qualifiers have been used to terms such kind of tourism, including halal, Islamic, Sharīʿah, and Muslim-friendly. There is currently a large disparity among stakeholders of such tourism in the understanding of the meaning and scope of these terms, which could lead to severe misunderstandings among them. This paper attempts to elucidate the similarities and differences of those terms and promote the appropriate usage for each term. It also discusses the implications of each term and how it may affect the perception of Muslim and non-Muslim travelers.